Futility, appropriate care, and orders not to resuscitate: Who makes decisions and how? - Lewis, Christopher D.; Ewer, Michael S. (SA Heart Journal, 2017)
Ethical issues in resuscitation arose once life-prolonging interventions advanced to the point where short-term cardiac resuscitation became plausible in patients in cases where imminent death was irreversible. The authors argue that ethical dilemmas arise from disputes over continued treatment when stakeholders either disagree about the meaning of appropriate care as a result of differing beliefs on the meaning of an acceptable outcome and/or the extent of a treatment’s probable efficacy. The authors conclude that even though communication and transparency can help prevent these ethical dilemmas, unavoidable conflict over proper interventions should be resolved through a decision-making process grounded in both medical reality and the principles of patient self-determination. Thoughtful regulatory guidance can aid the understanding of rights and responsibilities when the desirability, efficacy, and medical indication of life-prolonging interventions are in dispute. The authors outline such a process. The authors suggest that seeking clear regulation in this arena is a worthwhile ethical and practical objective for physicians to reduce both the likelihood of conflicts and the burden of unavoidable conflicts despite transparency and communication.